Answer: y = x/2 + 3
Step-by-step explanation:
The equation of a straight line can be represented in the slope-intercept form, y = mx + c
Where c = intercept
Slope, m = change in value of y on the vertical axis / change in value of x on the horizontal axis
change in the value of y = y2 - y1
Change in value of x = x2 -x1
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
Looking at the graph,
y2 = 6
y1 = 4
x2 = 6
x1 = 2
Slope,m = (6 - 4)/(6 - 2) = 2/4 = 1/2
To determine the intercept, we would substitute x = 2, y = 4 and m= 1/2 into y = mx + c. It becomes
4 = 1/2 × 2 + c
4 = 1 + c
c = 4 - 1
c = 3
The equation becomes
y = x/2 + 3
Use a calculator and divide
Answer:
Lynnette can wash 2111109 in 11 days
Step-by-step explanation:
Have a good day :)
You gotta remember that
![(f-g)(x)](https://tex.z-dn.net/?f=%28f-g%29%28x%29)
means
![f(x) - g(x)](https://tex.z-dn.net/?f=f%28x%29%20-%20g%28x%29)
.
So, in this case, f(x) is [4x - 3], g(x) is [x^3 + 2x].
So that : f(x)-g(x) = [4x-3] - [x^3+ 2x] = -x^3 + 4x - 2x - 3 = -x^3 + 2x - 3